Evaluation and validation of a multi-residue method based on biochip technology for the simultaneous screening of six families of antibiotics in muscle and aquaculture products. Issue 3 (3rd March 2016) - Gaudin, Valérie; Hedou, Celine; Soumet, Christophe; Verdon, Eric
ABSTRACT: The Evidence Investigator™ system (Randox, UK) is a biochip and semi-automated system. The microarray kit II (AM II) is capable of detecting several compounds belonging to different families of antibiotics: quinolones, ceftiofur, thiamphenicol, streptomycin, tylosin and tetracyclines. The performance of this innovative system was evaluated for the detection of antibiotic residues in new matrices, in muscle of different animal species and in aquaculture products. The method was validated according to the European Decision No. EC/2002/657 and the European guideline for the validation of screening methods, which represents a complete initial validation. The false-positive rate was equal to 0% in muscle and in aquaculture products. The detection capabilities CCβ for 12 validated antibiotics (enrofloxacin, difloxacin, ceftiofur, desfuroyl ceftiofur cysteine disulfide, thiamphenicol, florfenicol, tylosin, tilmicosin, streptomycin, dihydrostreptomycin, tetracycline, doxycycline) were all lower than the respective maximum residue limits (MRLs) in muscle from different animal origins (bovine, ovine, porcine, poultry). No cross-reactions were observed with other antibiotics, neither with the six detected families nor with other families of antibiotics. The AM II kit could be applied to aquaculture products but with higher detection capabilities from those in muscle. The detection capabilities CCβ in aquaculture products were respectively at 0.25, 0.10 and 0.5 of the respective MRL in aquaculture products for enrofloxacin, tylosin and oxytetracycline. The performance of the AM II kit has been compared with other screening methods and with the performance characteristics previously determined in honey.